Perception of pharmacy students in Malaysia on the use of objective structured clinical examinations to evaluate competence. - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Al-Efan, Qais Muhammad Ahmad (American Association of Colleges of Pharmacy, 2007)
Objectives. To assess bachelor of pharmacy students’ overall perception and acceptance of an objective structured clinical examination (OSCE), a new method of clinical competence assessment in pharmacy undergraduate curriculum at our Faculty, and to explore its strengths and weaknesses through feedback. Methods. A cross-sectional survey was conducted via a validated 49-item questionnaire, administered immediately after all students completed the examination. The questionnaire comprised of questions to evaluate the content and structure of the examination, perception of OSCE validity and reliability, and rating of OSCE in relation to other assessment methods. Open-ended follow-up questions were included to generate qualitative data. Results. Over 80% of the students found the OSCE to be helpful in highlighting areas of weaknesses in their clinical competencies. Seventy-eight percent agreed that it was comprehensive and 66% believed it was fair. About 46% felt that the 15 minutes allocated per station was inadequate. Most importantly, about half of the students raised concerns that personality, ethnicity, and/or gender, as well as interpatient and interassessor variability were potential sources of bias that could affect their scores. However, an overwhelming proportion of the students (90%) agreed that the OSCE provided a useful and practical learning experience. Conclusions. Students’ perceptions and acceptance of the new method of assessment were positive. The survey further highlighted for future refinement the strengths and weaknesses associated with the development and implementation of an OSCE in the International Islamic University Malaysia’s pharmacy curriculum.